Dicke superradiant heat current enhancement in circuit quantum electrodynamics - Gian Marcello Andolina; Paolo Andrea Erdman; Frank Noé; Jukka Pekola; Marco Schirò (Physical Review Research)
Controlling the flow of energy and heat at the microscale is crucial to achieve energy-efficient quantum technologies, for on-chip thermal management, and to realize quantum heat engines and refrigerators. Yet, the efficiency of current quantum technologies is affected by thermal noise, and efficient cooling of quantum devices remains challenging in various solid-state implementations such as superconducting circuits. Collective effects, such as the Dicke superradiant emission, have been exploited to enhance the performance of quantum devices. However, the inherently transient nature of Dicke superradiant emission raises questions about its impact on steady-state properties. Here, we study how to enhance the steady-state heat current flowing between a hot bath and a cold bath through an ensemble of N qubits, that are collectively coupled to the thermal baths. Remarkably, we find a regime where the heat current scales quadratically with N in a finite-size scenario. Conversely, when approaching the thermodynamic limit, we prove that the collective scenario exhibits a parametric enhancement over the noncollective case. We then consider the presence of a third uncontrolled parasitic bath, interacting locally with each qubit, that models unavoidable couplings to the external environment. Despite having a nonperturbative effect on the steady-state currents, we show that the collective enhancement is robust to such an addition. Finally, we discuss the feasibility of realizing such a Dicke heat valve with superconducting circuits. Our findings indicate that in a minimal realistic experimental setting with two superconducting qubits, the collective advantage offers an enhancement of approximately 10% compared to the noncollective scenario.